Independence and accountability of independent regulatory agencies: the case of Turkey - Cetin, Tamer; Sobaci, M. Zahid; Nargelecekenler, Mehmet (SPRINGER, 2016)
For a long time, governments have delegated their regulatory powers to independent regulatory agencies (IRAs). The aim is to reduce transaction costs and to ensure a credible commitment in the regulatory institutional structure. This paper discusses transition to IRAs in Turkey in terms of independence and accountability. To this aim, we firstly analyze the institutional foundations of transition to IRAs in Turkey from a political economy perspective and then measure their formal independence levels. We find that the pragmatic policies of the incumbent government regarding IRAs negatively influence their independence. This injures the credibility of regulatory commitment and increases the political transaction costs of regulatory process in Turkey.
Keywords: Regulatory agencies; Transaction costs; Credible commitment; Independence; Accountability; POLITICAL CONTROL; DELEGATION; INSTITUTIONS; INFORMATION; LIMITS; Business & Economics; Government & Law